1993
DOI: 10.4049/jimmunol.150.8.3161
|View full text |Cite
|
Sign up to set email alerts
|

CD28 engagement by B7/BB-1 induces transient down-regulation of CD28 synthesis and prolonged unresponsiveness to CD28 signaling.

Abstract: Costimulatory molecules on the APC regulate T cell growth by providing signals that regulate responses to TCR occupancy. One such molecule is B7/BB-1, which triggers a T cell activation pathway by binding the CD28 and/or CTLA-4 cell-surface molecules. Expression and signaling activity of CD28 have been shown to increase after T cell activation by various polyclonal activators. Here we show that CD28 expression and signaling activity in activated T cells decrease after ligand binding to CD28. Stimulation of CD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Since downmodulation of CD28 expression can be achieved in vitro through prolonged stimulation with specific peptide antigens 7 , or with cytokines like tumor necrosis factor-α (TNF-α) 8 , it can be hypothesized that the number of circulating CD28-T cells might represent a measure of the burden of prolonged previous immune stimulation. Moreover, downmodulation of CD28 expression can also be achieved in vitro through engagement with its ligands (CD80/CD86) 9 , and since this engagement is blocked by abatacept, we hypothesized that abatacept also prevents generation of the CD28-population. Indeed, we have shown that the number of CD28-T cells is reduced after therapy with abatacept 4 , and that such a decrease is correlated with clinical response.…”
mentioning
confidence: 99%
“…Since downmodulation of CD28 expression can be achieved in vitro through prolonged stimulation with specific peptide antigens 7 , or with cytokines like tumor necrosis factor-α (TNF-α) 8 , it can be hypothesized that the number of circulating CD28-T cells might represent a measure of the burden of prolonged previous immune stimulation. Moreover, downmodulation of CD28 expression can also be achieved in vitro through engagement with its ligands (CD80/CD86) 9 , and since this engagement is blocked by abatacept, we hypothesized that abatacept also prevents generation of the CD28-population. Indeed, we have shown that the number of CD28-T cells is reduced after therapy with abatacept 4 , and that such a decrease is correlated with clinical response.…”
mentioning
confidence: 99%